Current Advances in the Perioperative Treatment of Muscle-Invasive Bladder Cancer - Ursula Vogl; Giuseppe Salfi; Giovanna Pecoraro; Martino Pedrani; Ricardo Pereira Mestre; Marialuisa Puglisi; Fabio Turco (healthbook TIMES. Oncology Hematology, 2025)
Muscle-invasive bladder cancer (MIBC) is a highly aggressive disease with a significant risk of recurrence with metastatic disease. Neoadjuvant chemotherapy has been the preferred approach for cisplatin-eligible patients, with regimens such as dose-dense methotrexate, vinblastine, doxorubicin and cisplatin (ddMVAC), as well as gemcitabine plus cisplatin (GC). Recent trials adding immune checkpoint inhibitors to cisplatin-based chemotherapy in the perioperative setting have shown promising results. Notably, the phase III NIAGARA trial established durvalumab plus GC as a new standard of care for perioperative treatment of cisplatin-eligible patients with MIBC. For cisplatin-ineligible patients, comprising approximately half of the MIBC population, alternative treatment strategies are explored in clinical trials, including immunotherapy, antibody-drug conjugates (ADCs) and novel drug combinations. Furthermore, the emergence of circulating tumor DNA (ctDNA) as a biomarker for treatment guidance is under investigation for risk stratification and personalization of adjuvant immunotherapy. This review article highlights the current practice in MIBC management, focusing on neoadjuvant and perioperative treatment strategies, novel therapeutic approaches and the evolving role of biomarkers in guiding clinical decisions.